Family Ceratopogonidae - Ronderos, Maria Marcela; Díaz, Florentina; Marino, Pablo Ignacio; Ferreira Keppler, Ruth
Ceratopogonidae is placed in the infraorder Culicomorpha. Their common names are polvorines, manta blanca, chaquistes or jejenes (common name shared with Simuliidae) in Spanish speaking countries; mosquito pólvora or maruim in Brazil; and biting midges, no-see-ums or punkies in English speaking countries. It is an ancestral group, with numerous fossil records in amber from 17 to around 121 million years old. It is one of the most diverse family of Diptera, occurring on all continents except Antarctica and in most habitats, including deserts. The family includes six subfamilies, four of which are extant and worldwide in distribution, with 112 extant genera and 6,268 species. In addition, the fossil record includes another 284 extinct species and 21 extinct genera. Four subfamilies inhabit the Neotropical region: Leptoconopinae, Forcipomyiinae, Dasyheleinae and Ceratopogoninae including more than 1,226 species in 53 genera, of which, 16 are cosmopolitan. Females usually lay their eggs on or in organically rich aquatic or wet habitats where larvae complete their development and pupate. Oviposition microhabitats are very diverse. Eggs can be collected from field substrates and later placed in the laboratory in plastic containers to record time of hatching and subsequent development of larval stages I to IV. Alternatively, they can be taken from gravid females. Larvae and pupae can be collected from standing water, mud, detritus, slit, leaves and/or moist organic matter using pipettes and transported to the lab in plastic containers with water from their natural environment. Collected larvae and pupae should be examined to see life body shape, movements and general coloration because after fixation these characters are changed. A list of the terminology and morphology usually used in descriptions of larvae and pupae, as well as a table with all previous descriptions of each immature stage in Neotropical Region are provided. On the other hand, we present keys of larvae and pupae to the subfamily level. Fil: ...